Awareness, Behavior, and Gaps: A Survey-Based Analysis of Personal Hygiene, Home Safety, and Road Safety Practices - Neelesh Kumar Maurya; Gul Sirin; Faiza Farji; Vandita Mahanta (International Journal of Behavioral Sciences, 2026)
Personal hygiene and public safety remain two of the most critical yet behaviorally neglected pillars of community health in India. Despite decades of national health campaigns, a persistent gap continues to exist between what people know and what they actually do — particularly among urban youth. This cross-sectional, survey-based study examined awareness levels, behavioral practices, and compliance gaps across three interconnected domains: personal hygiene, home accident prevention, and road safety, among 32 respondents from urban, semi- urban, and rural settings in India. Data were collected using a structured 30-item Google Forms questionnaire covering demographic details, hygiene practices, household safety behaviors, and road safety knowledge. The sample was predominantly young (68.8% aged 18–25 years), female (59.4%), and urban (59.4%), reflecting the digital accessibility of the survey platform.Findings revealed a notable imbalance across the three domains. Personal hygiene awareness was relatively strong, with 84.4% of respondents consistently washing hands before meals and 87.5% practicing respiratory hygiene. Home safety compliance was equally encouraging, with 93.8% reporting consistent gas safety practices and 75% maintaining a first aid kit. Road safety, however, emerged as the most critical area of concern — 71.9% of respondents admitted to ignoring traffic rules in the absence of enforcement, and 37.5% reported skipping helmets or seatbelts when in a hurry, despite acknowledging road injuries as a serious public health threat.These findings confirm a deeply rooted knowledge–behavior gap, particularly in road safety, driven less by ignorance and more by attitudinal barriers such as time pressure (18.8%), lack of discipline (59%), and overconfidence (6.3%). The study underscores an urgent need for targeted, enforcement-integrated, and youth-centered behavioral interventions across all three safety domains in India.
Keywords: Handwashing; India; Personal hygiene; behavior change; home accident prevention; public safety; road safety